Rainwater Harvesting Systems (RWHS): The Multi-Level Perspective towards Sustainability Transition - Juele, Ingrid; Lapong, Edward (Journal of Interdisciplinary Perspectives, 2024)
Water scarcity, severe flooding, environmental concerns, and the drive for sustainability have positioned rainwater harvesting systems (RWHS) as a key element in sustainable resource management. However, overcoming adoption challenges remains crucial. This study investigates the potential of RWHS to address water scarcity and flooding in the City of Koronadal, Philippines, using Frank Geels' Multi-Level Perspective (MLP) framework and Jan Rotmans' Sustainability Transition concepts. Through surveys, interviews, and document analysis, the study examines the interplay of landscape pressures (such as climate change, water scarcity, and national laws on climate change and resource management), socio-technical and political regimes (including existing water management practices, local policies, and regulatory frameworks), and technological niches in shaping the city's water future. The findings reveal that although awareness of water scarcity and climate change is high, RWHS adoption is hindered by a lack of policy support, financial constraints, technical limitations, and institutional barriers. The study also identifies opportunities for RWHS to alleviate flooding, reduce reliance on traditional water sources, and promote sustainable water management. The research concludes by proposing a comprehensive implementation scheme for RWHS in Koronadal City. This scheme integrates policy interventions, financial incentives, technical support, and community engagement to overcome existing barriers and facilitate a transition toward a more resilient and water-secure future.